PRONUNCIATION OF PREFIXED WORDS IN SPEECH: THE IMPORTANCE OF SEMANTIC AND INTERSUBJECTIVE PARAMETERS LINGVISTIKA (Conferencea, 2022)
This article provides information about the pronunciation of prefixed words in speech. The author clearly and fully explains the pronunciation of prefixed words. In addition, special emphasis is placed on the semantic changes that occur in the meanings of words. This article will help the user to better understand the structural forms of the language.